2021
DOI: 10.1038/s41598-021-86928-2
|View full text |Cite
|
Sign up to set email alerts
|

Validation of three predictive models for suboptimal cytoreductive surgery in advanced ovarian cancer

Abstract: The standard treatment for advanced ovarian cancer (AOC) is cytoreduction surgery and adjuvant chemotherapy. Tumor volume after surgery is a major prognostic factor for these patients. The ability to perform complete cytoreduction depends on the extent of disease and the skills of the surgical team. Several predictive models have been proposed to evaluate the possibility of performing complete cytoreductive surgery (CCS). External validation of the prognostic value of three predictive models (Fagotti index and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 31 publications
1
19
0
2
Order By: Relevance
“…In Thailand, advancedstage became a significant predictor for suboptimal surgery (OR = 4.78, p < 0.001) [17]. We found that age did not significantly differ among two groups of debulking surgery, similar to prior study [57]. In contrast, a multivariate analysis from Gu et al [58] found age >60 years become a significant predictor for suboptimal debulking surgery with OR 2.39 possibly due to younger cut-off of elderly we used in this study.…”
Section: Suboptimal Debulking Surgery Predictorssupporting
confidence: 86%
See 1 more Smart Citation
“…In Thailand, advancedstage became a significant predictor for suboptimal surgery (OR = 4.78, p < 0.001) [17]. We found that age did not significantly differ among two groups of debulking surgery, similar to prior study [57]. In contrast, a multivariate analysis from Gu et al [58] found age >60 years become a significant predictor for suboptimal debulking surgery with OR 2.39 possibly due to younger cut-off of elderly we used in this study.…”
Section: Suboptimal Debulking Surgery Predictorssupporting
confidence: 86%
“…The results showed that serous EOC (OR = 8.25) and FIGO staging (OR = 11.13) significantly enhanced the chance to experience suboptimal surgical cytoreduction. The prior study reaffirmed that subtype [55], particularly serous EOC [56] and stage of disease [55], [57], were associated significantly and became predictors to suboptimal debulking surgery. In Thailand, advancedstage became a significant predictor for suboptimal surgery (OR = 4.78, p < 0.001) [17].…”
Section: Suboptimal Debulking Surgery Predictorsmentioning
confidence: 85%
“…To optimize that rate, different calculation models included the findings of CT scans, laparoscopy, and laparotomy, identifying a marker constellation of a PCI of 20 and more and bowel obstruction as significant for incomplete cytoreduction. As bowel obstruction is rather rare despite high tumor loads and reason for surgical intervention anyhow, this model may not be suitable for all patients in everyday business to prevent futile surgery ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies developed scoring systems for predicting operative results in PDS for patients with AOC (16,(18)(19)(20)(21). Among them, the predictive value has been mainly focused on suboptimal surgery, and the data on their predictive values for complete PDS are controversial.…”
Section: Discussionmentioning
confidence: 99%